VALIDITAS VIDEO PEMBELAJARAN KONSEP DAN APLIKASI WARNA DALAM DESAIN BUSANA UNTUK SISWA KELAS X BUSANA SMKN 3 PEKANBARU - Wahyuni, Tri; Aryati, Yulia; Yusmerita; Nelmira, Weni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning the concept and application of color in fashion design is still dominated by manual lecture and demonstration methods with limited media, so students have difficulty visualizing concepts and their application. This study aims to analyze the validity of video learning concepts and applications of color in fashion design for students of class X Fashion SMK Negeri 3 Pekanbaru. The research uses the Research and Development (R&D) method with a 4D development model which includes the define, design, develop, and disseminate stages. Validation was carried out by material experts, media experts, and linguists using the Likert scale questionnaire. The data was analyzed in a quantitative descriptive manner through the calculation of the eligibility percentage. The results of the study show that learning videos obtain a very valid category in terms of material, media, and language so that they are declared suitable for use as learning media. Thus, the developed learning videos meet the eligibility criteria and can be used to support the learning of concepts and the application of color in fashion design.